Colonial geopolitics and local cultures in the Hellenistic and Roman East (3rd century BC - 3rd century AD) = Géopolitique coloniale et cultures locales dans l'Orient hellénistique et romain (IIIe siècle av. J.-C. - IIIe siècle ap. J.-C.) - Bru, Hadrien,; Dumitru, Adrian George,; Sekunda, Nick, 1953- (Archaeopress Archaeology, 2021)
What changes in the material culture can we observe, when a state is overwhelming a local population with soldiers, katoikoi, and civil officials or merchants? What were the mutual influences between native and colonial cultures? This collection addresses these questions and many more, focusing on the Hellenistic and Roman East.